2020
DOI: 10.1088/1742-6596/1641/1/012087
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparison and Optimized Algorithm Classification

Abstract: The current development of technology is quite rapidly not disengaged in a large data processor covering of all areas such as information technology, computer science, medicine, finance and other. This brings a large computing effect in identifying the processing of data. In data analysis for very large data, data processing is very much needed, in this study the authors propose data mining method as a solution to a large data processing problem, data mining is divided into several techniques including classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Classification is how to place specific objects into a group based on their nature. This method aims to study the different functions that describe each of the data selected into one of the predefined groups of classes [13].…”
Section: Methodsmentioning
confidence: 99%
“…Classification is how to place specific objects into a group based on their nature. This method aims to study the different functions that describe each of the data selected into one of the predefined groups of classes [13].…”
Section: Methodsmentioning
confidence: 99%
“…The researchers analyzed and tested five algorithms classification using four different datasets as a tool for big data classification problems. The results of the study showed that in using the UCI knowledge base of 4 datasets to calculate AUC values, the SVM method outperformed the 4 comparative methods [14]. Kalita et al researchers designed a new framework which uses new optimization modules Knowledge Based Search (KBS) and Moth-Flame Optimization (MFO) to perform optimization and efficiently train SVMs in a dynamic environment [15].…”
Section: Related Workmentioning
confidence: 99%
“…C.45 is a method and prediction that is very strong and very widely used. C4.5 used information gain to select the attributes that will be used for object separation [22].…”
Section: C45 Algorithmmentioning
confidence: 99%